(untitled) (Research, Society and Development, 2020)
The presence of anterosuperior diastemas can cause functional, aesthetic and psychological problems. With the evolution of dental materials, the rehabilitation of these cases using composite resin directly facilitated the treatment and enabled excellent results. This work aims to report a clinical case in which diastema closure and teeth resuscitation in the anterosuperior region were performed by means of direct restoration in composite resin, prioritizing the conservative technique in order to reestablish the aesthetics and harmony of the smile, in addition to patient’s self-esteem. A 43-year-old female patient reported dissatisfaction with the appearance of her smile due to color and a diastema located in the region of the central incisors. Then, home teeth whitening, diagnostic waxing, making the palatal silicone guide, composite resin restorations, finishing and polishing were performed. The use of composite resins in a direct way optimizes clinical time, presents better cost-benefit and there is no need to wear the dental structure, thus obtaining a conservative and aesthetic treatment. The completion of the diagnostic wax-up allows the predictability of the result, and the patient, together with the dental surgeon, can view and give an opinion on the same in terms of shape and size. In this way, following the restorative protocol carefully, the success of the technique and the final result was achieved, reaching the clinical aesthetic concepts and the patient’s expectations.